Celebrity ambassador/celebrity endorsement – takes a licking but keeps on ticking. (4th July 2019) - Proctor, Tony; Kitchen, Philip J.
Abstract: The paper examines the use of advertising and celebrity endorsement in promoting wristwatches from the beginning of the 20th century up until today. It shows a progression from simple informational advertisements stressing the technical, aesthetic and social appeals of the watches to more complex ones appealing to self-image and the use of celebrity endorsement. However, some – albeit not all – luxury wristwatch manufacturers have abandoned their use of celebrity endorsers. We note the need for businesses to undertake advertising aimed at appealing to consumer self-image, often reinforced by celebrity endorsement. The paper explores why the celebrity endorsement of brands may be effective or otherwise. We question, however, the cost-effectiveness of celebrity endorsement, and whether methods such as parasocial advertising through social media sites may offer an alternative. Like the brands they promote, advertising theories also have life cycles and the need to find new theories and update or abandon existing ones continues apace.